2018
DOI: 10.4236/ojog.2018.85058
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Accuracy of Automated Fetal Heart Echocardiography by Five Dimensional Compared to Two-Dimensional Ultrasound in the Second Trimester of Pregnancy

Abstract: Objective: To compare the diagnostic accuracy of Fetal Intelligent Navigation Echocardiography (FINE) method by Five-Dimensional Ultrasound in automated fetal heart examination to conventional fetal heart examination by Two-Dimensional ultrasound in second trimester pregnancy. Methods: 90 normal singleton pregnancies at the second trimester were enrolled in this prospective study. Fetal heart was examined by Two-Dimensional Ultrasound (2D US) and Five-Dimensional Ultrasound (FINE). Paired numerical data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Moreover, other groups have demonstrated that FINE works well in generating three specific abnormal cardiac views in cases of fetal D-transposition of the great arteries [ 35 ]. This is comparable in accuracy to conventional 2D fetal cardiac examination in normal second trimester fetuses with a significant reduction in examination time [ 36 ].…”
Section: Introductionmentioning
confidence: 87%
“…Moreover, other groups have demonstrated that FINE works well in generating three specific abnormal cardiac views in cases of fetal D-transposition of the great arteries [ 35 ]. This is comparable in accuracy to conventional 2D fetal cardiac examination in normal second trimester fetuses with a significant reduction in examination time [ 36 ].…”
Section: Introductionmentioning
confidence: 87%
“…In cases of CHD, FINE showed a sensitivity of 98% and a specificity of 93% [ 31 ]. Other groups have demonstrated that FINE works well in cases of fetal D-transposition of the great arteries [ 32 ] and works as well as traditional 2D fetal echocardiography with a significantly lower investigation time [ 33 ]. Our data indicated the applicability of FINE in different states of investigator experience [ 30 ] and in inconvenient fetal spine positions [ 34 ].…”
Section: Introductionmentioning
confidence: 99%